Investigate supply chain dynamics using the beer game platform - Xue, Yuanyuan. (2009)
Supply chain is a dynamic system in which not only customer demands and enterprises' capabilities vary over time, but also supply chain relationships. Many supply chain problems and issues are directly or indirectly related to supply chain dynamics, also called BuUwhip Effect. Most of the firms focus their attention on reducing uncertainty through supply chain collabotation with their partners. Beer Game was designed by Sloan's System Dynamics Group at MIT to help participants understand the supply chain dynamics better. However, the old web-based beer game developed at NTU's Center for Supply Chain Management only can be played on a single computer and the input model for the old beer game was too simple to simulate the real-life situation. In this dissertation, a new web-based beer game is developed, where players can play against each other over internet. A probablistic model has also been proposed to generate the customer's demands, which simulate the real-life situation much better. With the help of the new beer game system, various policies of supply chain collaboration and information sharing are tested, confirming that collaboration and information sharing will certainly reduce the cost for the entire supply chain. The new beer game system not only can help student to understand the basics of supply chain dynamics better but it also can be a platform to test various supply chain management policies.